2008
DOI: 10.1121/1.2980519
|View full text |Cite
|
Sign up to set email alerts
|

Waveguide invariant broadband target detection and reverberation estimation

Abstract: Reverberation often limits the performance of active sonar systems. In particular, backscatter off of a rough ocean floor can obscure target returns and/or large bottom scatterers can be easily confused with water column targets of interest. Conventional active sonar detection involves constant false alarm rate (CFAR) normalization of the reverberation return which does not account for the frequency-selective fading caused by multipath propagation. This paper presents an alternative to conventional reverberati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…It has been observed that reverberation intensity has regular striations in the time-frequency distribution in ref. [8]. However, in the paper, the theoretical derivation is different from that in ref.…”
Section: Introductionmentioning
confidence: 57%
“…It has been observed that reverberation intensity has regular striations in the time-frequency distribution in ref. [8]. However, in the paper, the theoretical derivation is different from that in ref.…”
Section: Introductionmentioning
confidence: 57%
“…This work is similar to work in other papers [7], [8], [9] where the Generalized Hough Transformation was also applied to evaluate spectral information.…”
Section: Track Hypothesis Testingmentioning
confidence: 62%
“…Goldhahn [7], [8] demonstrated its usability to improve noise estimation for ocean bottom reverberation and thus target and clutter return discrimination. Turgut [9] investigated the invariance principle for mid-frequency to estimate the invariance parameter value and possible target kinetics on simulated and experimental data.…”
Section: Introductionmentioning
confidence: 99%
“…In [25], Goldhahn et al uses the waveguide invariant to describe reverberation in active sonar returns, allowing for an improved ability for target detection.…”
Section: Active Sonarmentioning
confidence: 99%
“…The waveguide invariant has been used for a wide range of applications such as: passive range estimation [58,56,62], matched field processing [59,23], active sonar [49,27,25], array processing [37,57,66], time-reversal mirrors [32,54,38,39], and more (See Appendix A for a complete review of the waveguide invari-ant literature). Despite its many uses, the waveguide invariant is not well studied compared to other ocean-acoustic phenomena.…”
Section: Introductionmentioning
confidence: 99%